UPAYA PENINGKATAN BUDAYA K3 (KESELAMATAN DAN KESEHATAN KERJA) PADA UKM BENGKEL LAS PINTU HARMONIKA “JAYA MANDIRI” DENGAN PENGGUNAAN ALAT PELINDUNG DIRI - I Wayan Joniarta; Anak Agung Alit Triadi; Arif Mulyanto; I Dewa Ketut Okariawan; Paryanto Dwi Setyawan (Jurnal Abdi Insani, 2022)
Counseling and socialization of the use of Personal Protective Equipment (PPE) is one of the efforts to support Occupational Health and Safety. Welding workshop "Jaya Mandiri" is an activity partner that requires this. The purpose of the activity is to increase awareness and skills on the importance of using PPE when working. For this reason, making SOPs for the use of PPE is a mandatory procedure to start a job. The method used is counseling and demonstration of the use of PPE then followed by the use of PPE while working. The results of the activities were analyzed using a Likert scale. After that, the SOP and supervision methods were determined by the workshop owner in the use of PPE so that it became a habit to become a culture. The results obtained after counseling and demonstration of PPE are an increase in understanding and skills in the use of PPE from employees. From the results of the Likert scale analysis, the highest was the use of welding safety helmets after counseling 74.29% from the previous average of 31.43%. The lowest result is the use of apron (Apron) 57.14% before 22.86%. It was also found that one of the employees who had the highest understanding and skills in the use of all PPE, namely Munahar, reached 84% after counseling from only 40% previously. The skills and discipline of employees in the use of PPE still need to be improved by means of supervision by SME owners. The service implementation team together with the workshop owners and employees agreed to make an SOP in supervising the use of PPE to support K3 so that it becomes a good and entrenched habit.